Oral hygiene among North Indian population - Dhruvendra Lal; Kavisha Kapoor Lal (Faculty of Dentistry, Universitas Trisakti, 2023)
Background: Oral health is a vital component of overall health and well-being and is an important indicator of healthy living and quality of life. According to the Global Burden of Disease Study 2019, approximately 3.5 billion people worldwide have oral diseases. Objective: This study assessed the level of oral hygiene in a rural community in North India. Materials and Methods: This community-based cross-sectional study included randomly chosen men and women from a rural area of the Ludhiana district of Punjab from August 2021 to February 2022 using the World Health Organization (WHO) Oral Health Questionnaire. Results: This study included 405 participants, comprising 205 (50.6%) men and 200 (49.4%) women, with a mean age of 44.5 + 16.7 years. It was found that only 17.3% of the participants had good status of their gums and teeth, without caries, compared with 17.8% who had poor or extremely poor status. In addition, 54.2% of the participants reported experiencing pain and discomfort in their gums and teeth due to poor oral hygiene. Conclusion: Only a small percentage of our rural cohort had good oral hygiene, indicating a need for increased awareness initiatives.